The impact of BST1 rs4698412 variant on Parkinson’s disease progression in a longitudinal study - Hao-Ling Xu; Hao-Ling Xu; Yu Yang; Yu Yang; Yu Yang; Li-Na Chen; Li-Na Chen; Yun-Jing Li; Yun-Jing Li; Guo-En Cai; Guo-En Cai; Ying-Qing Wang; et al. (Frontiers in Aging Neuroscience)
BackgroundWhile the BST1 rs4698412 variant demonstrates a robust association with Parkinson’s disease (PD) susceptibility, its role in modulating PD progression remains unexplored.ObjectivesTo evaluate differences in the progression of motor symptoms and cognitive function between PD patients carrying the BST1 rs4698412 A-allele variant and GG homozygotes.MethodsBaseline clinical data were collected during their initial visits. Disease severity was assessed using the UPDRS-III scale, while cognitive status was evaluated through the MMSE scale. Follow-up visits were conducted at the same center. Linear mixed-effects models were utilized to compare the rate of changes in motor and cognitive features between the two groups.ResultsA total of 182 PD patients with 74 classified as GG carriers and 108 as GA/AA carriers were enrolled. No significant differences were observed in baseline demographic factors or clinical characteristics. Linear mixed-effects models revealed that GA/AA carriers exhibited a greater rate of change in UPDRS-III score compared with GG carriers (difference of −2.091[0.691] points per year, P = 0.003). However, no statistically significant difference in the estimated progression rate of MMSE score was found between the two groups (difference of −0.106 [0.217] points per year, P = 0.627).ConclusionPD patients carrying the BST1 rs4698412 A-allelic variant showed more pronounced motor function deterioration than GG carriers, suggesting that BST1 rs4698412 may serve as a genetic risk factor for disease progression in PD.